Optimalisasi Bisnis Pengrajin Udeng Pacul Gowang Sidoarjo melalui Pembukuan Keuangan Digital dan Social Media Marketing - Warmana, G. Oka; Sholihah, Dewi Deniaty; Trisnaningtyas, Januari Pratama Nurratri (Universitas Nusantara PGRI Kediri, 2023)
Global market demands encourage Udeng Pacul Gowang craftsmen to continuously innovate and improve the use of technology in all aspects so that their products can compete in the free market. Even though the potential for this business is quite large, many Udeng Pacul Gowang craftsmen still experience problems in achieving success in their business. The solution offered is to provide training in order to increase literacy and skills to manage Android-based digital financial accounting through the